2020
DOI: 10.1097/rlu.0000000000003216
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Detection of Malignant Melanoma Brain Recurrence on 68Ga–Prostate-Specific Membrane Antigen PET/CT

Abstract: A 76-year-old man with a prior medical history of resected malignant melanoma of the skull underwent 68Ga–prostate-specific membrane antigen (PSMA) PET/CT due to rising tumor markers of a known prostate carcinoma. Unexpected high 68Ga-PSMA brain uptake was encountered around the surgical cavity in the skull with initially no specific structural changes on anatomical imaging. Successive CT and MRI eventually revealed local melanoma brain recurrence at this site. This interesting case demonstrates the diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
1
6
0
1
Order By: Relevance
“…Brain uptake is not specific for stroke on PSMA PET, as prostate metastases, primary brain tumors, and nonprostate brain metastases have all been demonstrated. [6][7][8] The patient was admitted to the neurology service for medical management as he was not a candidate for tPA. This case demonstrates a rare occurrence of a subacute ischemic stroke being detected by PSMA PET/CT.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Brain uptake is not specific for stroke on PSMA PET, as prostate metastases, primary brain tumors, and nonprostate brain metastases have all been demonstrated. [6][7][8] The patient was admitted to the neurology service for medical management as he was not a candidate for tPA. This case demonstrates a rare occurrence of a subacute ischemic stroke being detected by PSMA PET/CT.…”
Section: Figurementioning
confidence: 99%
“…Although other cases of PSMA uptake in strokes have been reported, 1,4,5 this case is unique as it demonstrates this phenomenon occurring with 18 F-piflufolastat and the same-day clinical and MR evaluation. Brain uptake is not specific for stroke on PSMA PET, as prostate metastases, primary brain tumors, and nonprostate brain metastases have all been demonstrated 6–8 . The patient was admitted to the neurology service for medical management as he was not a candidate for tPA.…”
mentioning
confidence: 99%
“…Parihar et al demonstrated avid brain metastasis uptake with 68Ga-PSMA-HBED-CC PET/CT in a patient with prostate cancer (15). There are additional reports of avid uptake of PET PSMA molecular imaging agents in renal cell carcinoma (16), thyroid cancer (17), adenoid cystic carcinoma of the parotid gland (18), and melanoma (19).…”
Section: Prostate Specific Membrane Antigen Ligandsmentioning
confidence: 99%
“…Furthermore, 68 Ga-PSMA PET/CT has been found as a potentially beneficial imaging tool in the evaluation of both primary and metastatic brain tumors due to the absence of physiological uptake of 68 Ga-PSMA in the normal brain parenchyma resulting in high tumor-to-background ratio compared with 18 F-FDG PET/CT 6 . Incidental PSMA-positive brain metastasis has been shown in various malignancies 7–11 . Yet brain metastasis in prostate carcinoma is uncommon, 68 Ga-PSMA–avid brain metastasis of prostatic cancer has also been reported in the literature 12,13 .…”
mentioning
confidence: 99%
“…6 Incidental PSMA-positive brain metastasis has been shown in various malignancies. [7][8][9][10][11] Yet brain metastasis in prostate carcinoma is uncommon, 68 Ga-PSMA-avid brain metastasis of prostatic cancer has also been reported in the literature. 12,13 In this case, the difficulty was coexisting prostatic and gastric carcinoma, which can both metastasize to the brain.…”
mentioning
confidence: 99%